شروط الراوي الذي يحتج به عند القنوجي في كتابه "عون الباري بحل أدلة البخاري": Conditions for accepting the transmitter of the hadith with Alkanouji During his book “Aoun Al-Bari solving the evidences of Al-Bukhari” - Ibrahim almashjari; Shumsudin Yabi; Almulla, Mohamad sadeq abdelrahman; alkarbi , Mohammed ali hamad (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث تتلخص هذه الدراسة في مبحث شروط الراوي الذي يحتج به عند القنوجي في كتابه "عون الباري بحل أدلة البخاري"، حيث أن مشكلة البحث هي كيف سيستخرج الباحث شروط الراوي الذي يحتج به من كتاب عون الباري بحل أدلة البخاري، وكيف سيقوم بتحليل هذه الشروط ودراستها والاستفادة منها مدعوما بما قرره العلماء من قبله في هذا الباب، ويهدف الباحث إلى جمع واستقراء ما قرره العلامة القنوجي رحمه الله على مبحث شروط الراوي الذي يحتج به في شرحه، ثم تحليل هذه النقولات واستخراج الفوائد المتعلقة بالموضوع مع ما قرره العلماء من قبله ومن بعده، وسيسير الباحث في منهجيته على المنهج الاستقرائي والتحليلي؛ وذلك لأن الباحث سيقوم باستقراء شرح القنوجي وبعد أن يجتمع عنده شواهد على شروط الراوي الذي يحتج به فإنه سيقوم بتحليل هذه الشواهد على موضوعه والاستفادة منها، وستكون نتيجة البحث بأن القنوجي في شرحه اشترط لصحة الاحتجاج بالراوي في روايته هو أن تتم عنده شرطي العدالة والضبط. ABSTRACT This study is summarized in the study of the carrier conditions that must be fulfilled according to Al-Qanuji in his book “Awn Al-Bari bi-halal Divon Al-Tafal”, Since the problem of the research is how the researcher will extract the conditions of the carrier whom he cites from the book of Aoun Al-Bari by solving Al-Bukhari’s evidence, and how will he analyze, study and benefit from these conditions supported by what the scholars before him have decided in this section? The researcher aims to collect and extrapolate what the scholar Al-Qanuji, may allah have mercy on him, decided on the topic of the conditions of the carrier, which he uses as evidence in his explanation. Then analyze these quotes and extract the benefits related to the topic along with what the scholars before and after him decided. The researcher will follow the inductive and analytical approach in his methodology. This is because the researcher will extrapolate Al-Qanuji’s explanation, and after he has collected evidence on the conditions of the carrier whom he uses as evidence, he will analyze this evidence on his subject and benefit from it. The result of the research will be that Al-Qanuji, in his explanation, stipulated for the validity of invoking the narrator in his narration that the two conditions of justice and control be met with him.